Efficiency of Government Spending For Human Development Some Districts in Central Java During 2008 - 2012 - atmanti, hastarini dwi (Journal of Developing Economies, 2016)
Human development is a good indicator to measure the progress of a nation.Welfare of a nation measured not only from the gross domestic product, but also from the human development aspect, which include education and public health. The paper represented education and health aspect by the Human Development Index (HDI) while the economic performance is reflected by the value of Purcashing Power Parity (PPP) index. This study analyzes the efficiency of government spending on human development using Data Envelopment Analysis (DEA). The study shows that the level of efficiency of government spending on human development in some districts in Central Java during 2008 – 2012 is more than 90%. Keywords: Government Spending, Human Development, EfficiencyJEL: D61